1993
DOI: 10.1210/endo.132.4.8384994
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of progesterone secretion by recombinant follistatin-288 in human granulosa cells.

Abstract: The effects of recombinant human follistatin (follistatin-288) on basal and hCG-stimulated progesterone secretion were examined in cultured human granulosa cells. Follistatin increased progesterone secretion in a dose-dependent manner. However, follistatin did not augment hCG- or cAMP-stimulated progesterone secretion. Time-course analysis revealed that follistatin increased progesterone secretion after 24 h of incubation. Follistatin also enhanced basal, but not hCG-stimulated, 20 alpha-hydroxyprogesterone ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…We show here for the first time that PGE 2 is able to increase FS production in ovarian granulosa cells, and this finding supports the idea that FS might have luteotropic effects in the human ovary. A luteotropic role for FS in human ovary is also supported by recent studies showing that FS is able to increase human GL cell progesterone production [53], probably by blocking the effects of endogenously produced activins [29]. Although no studies on the stimulatory effect of PGE 2 on FS production have been previously described in ovarian cells, PGE2 has been reported to induce FS mRNA in rat mesangial cells [54].…”
Section: Discussionmentioning
confidence: 80%
“…We show here for the first time that PGE 2 is able to increase FS production in ovarian granulosa cells, and this finding supports the idea that FS might have luteotropic effects in the human ovary. A luteotropic role for FS in human ovary is also supported by recent studies showing that FS is able to increase human GL cell progesterone production [53], probably by blocking the effects of endogenously produced activins [29]. Although no studies on the stimulatory effect of PGE 2 on FS production have been previously described in ovarian cells, PGE2 has been reported to induce FS mRNA in rat mesangial cells [54].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, although follistatin increases progesterone secretion in a dose-dependent manner, it does not augment hCG-stimulated progesterone secretion [30]. We therefore speculate that the follicular volume, and P4, T and ASD levels in the follicular fluid are the cumulative products of high constant FSH stimulation and the ovulatory dose of hCG administered during the process of COH, not necessarily in accordance with the mRNA expression of follistatin at the moment of oocyte retrieval.…”
Section: Discussionmentioning
confidence: 76%
“…In addition to neutralizing the action of activin, we have also shown that FS alone stimulates basal progesterone, 20ct-hydroxyprogesterone and cAMP accumulation in the human granulosa-luteal cells [49]. FS also stimulates basal estradiol production [Khora- [50] , It is conceivable, therefore, that FS may have actions which are independent of activ in.…”
Section: Biological Actions Of Foiiistatinmentioning
confidence: 97%